MAIN FACTORS AFFECTING THE QUALITY OF THE RECOMMENDED COMBINED ANTISPASMODIC TABLETS - Yunusova Kholida Mannanovna,; Ismailova Mukhayyo Karimovna,; Ilhamova Nargiza Bakhtiyarovna,; Jaloliddinova Muattar Bakhtiyarovna,; Anvarova Farangiz Jamshidovna, (Utilitas Mathematica, 2025)
The results of research on the development of combined tablets recommended as an antispasmodic drug based on simethicone and drotaverine hydrochloride are presented. The main factors influencing the quality of the recommended combined antispasmodic tablets have been studied.